Gadamer for architects - Kidder, Paul (Thinkers for architects., 2013)
"Providing a concise and accessible introduction to the work of the twentieth century's celebrated German philosopher, Hans-Georg Gadamer, this book focuses on the aspects of Gadamer's philosophy that have been the most influential among architects, educa